Connecting structure to function with the recovery of over 1000 high-quality metagenome-assembled genomes from activated sludge using long-read sequencing - Caitlin M. Singleton (Nature Portfolio, 2021)
Microbes play key roles in wastewater treatment. Here, Singleton et al. use long-read and short-read sequencing to recover 1083 high-quality metagenome-assembled genomes from 23 wastewater treatment plants, and combine this information with amplicon data, Raman microspectroscopy and FISH to reveal functionally important lineages.